Facility readiness to remove subdermal contraceptive implants in 6 sub-Saharan African countriesAJOG Global Reports at a Glance - Leigh Senderowicz, ScD; Celia Karp, PhD; Brooke W. Bullington, BA; Katherine Tumlinson, PhD; Linnea Zimmerman, PhD; Funmilola M. OlaOlorun, PhD; Musa Sani Zakirai, PhD (Elsevier, 2022)
OBJECTIVE: This study aimed to estimate the proportion of health facilities without the capability to remove contraceptive implants and those that have the capability to insert them and to understand facility-level barriers to implant removal across 6 countries in sub-Saharan Africa. STUDY DESIGN: Using facility data from the Performance Monitoring for Action in Burkina Faso, the Democratic Republic of Congo, Ethiopia, Kenya, Nigeria, and Uganda from 2020, we examined the extent to which implant-providing facilities (1) lacked necessary supplies to remove implants, (2) did not have a provider trained to remove implants onsite, (3) could not remove deeply placed implants onsite, and (4) reported any of the above barriers to implant removal. We calculated the proportion of facilities that report each barrier, stratifying by facility type. RESULTS: Between 31% and 58% of implant-providing facilities reported at least 1 barrier to implant removal in each country (6 sub-Saharan African countries). Lack of trained providers was the least common barrier to implant removal (0%-17% of facilities), whereas lack of supplies (17%-44% of facilities) and the inability to remove a deeply placed implant (16%-42%) represented more common obstacles to removal. Blades and forceps were commonly missing supplies across all 6 countries. Barriers to implant removal were less commonly reported at hospitals than at lower-level facilities in all countries except Burkina Faso. CONCLUSION: This multicountry analysis showed that facility-level barriers to contraceptive implant removal are widespread among facilities that offer implant insertion. By preventing users from being able to discontinue their implants on request, these barriers pose a threat to contraceptive autonomy and reproductive health.